If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(m + 5) = 22 Reorder the terms: 7(5 + m) = 22 (5 * 7 + m * 7) = 22 (35 + 7m) = 22 Solving 35 + 7m = 22 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + 7m = 22 + -35 Combine like terms: 35 + -35 = 0 0 + 7m = 22 + -35 7m = 22 + -35 Combine like terms: 22 + -35 = -13 7m = -13 Divide each side by '7'. m = -1.857142857 Simplifying m = -1.857142857
| 8-n=34 | | 7nsquared+7=12n | | 2(4x+3)+6= | | -56=88-9x | | 29-7x=28x-28 | | 9+14x+5x=180 | | 7-2f=1.98 | | 10-2y+4x=0 | | -7[4+7(-5+7)]+16= | | 50+3b=134 | | 3(1)=3 | | 7x+6=2z+2 | | 12x-13=-6x | | 6a-9-8a+5a= | | 5x+200=3x-300 | | -23n+13n+47-5n=-28 | | 3l+4-4l=-3 | | 53+18w=c | | 7x-4=37 | | 3(t-3)-2t=-30 | | (2m+3t)(3m-4t)= | | y=6000(1+0.04)5 | | 9x-8=8x+1 | | x^3-13x^2-2x+26=0 | | 7-3x-(-5x+2)+1+7x=5x | | 2x+4x-9x+7= | | 5(20x+25)=925 | | 10*xy+90=72x | | 12y-5y-7+4= | | 10x-50=7x+1 | | x-(5-2x)=1+(2+x) | | 2+(-3)(4)-(-5)= |